2020
DOI: 10.1186/s12906-020-02940-5
|View full text |Cite
|
Sign up to set email alerts
|

Polygonum multiflorum extract support hair growth by elongating anagen phase and abrogating the effect of androgen in cultured human dermal papilla cells

Abstract: Background: Dermal papilla cells (DPCs) play a key role in hair growth among the various cell types in hair follicles. Especially, DPCs determine the fate of hair follicle such as anagen to telogen transition and play a pivotal role in androgenic alopecia (AGA). This study was performed to elucidate the hair growth promoting effects of Polygonum multiflorum extract (PM extract) in cultured human DPCs and its underlying mechanisms. Methods:The effects of PM extract on cultured DPCs were investigated. Cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
0
30
0
1
Order By: Relevance
“…Quercitrin administration resulted in a decrease in mRNA expression of Bad, although the mRNA and protein expression of Bcl-2 increased after treatment of cultured hDPCs with 10 nM and 100 nM quercitrin [23]. PM extract also showed an increase in Bcl-2 mRNA expression and a decrease in Bad expression in hDPCs [30]. Panax ginseng extract inhibited apoptosis in Dickkopf-1 (DKK-1)-induced ORS keratinocytes as determined by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining [56].…”
Section: Apoptosismentioning
confidence: 90%
See 1 more Smart Citation
“…Quercitrin administration resulted in a decrease in mRNA expression of Bad, although the mRNA and protein expression of Bcl-2 increased after treatment of cultured hDPCs with 10 nM and 100 nM quercitrin [23]. PM extract also showed an increase in Bcl-2 mRNA expression and a decrease in Bad expression in hDPCs [30]. Panax ginseng extract inhibited apoptosis in Dickkopf-1 (DKK-1)-induced ORS keratinocytes as determined by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining [56].…”
Section: Apoptosismentioning
confidence: 90%
“…2,3,5,4-Tetrahydroxystilbene-2-O-D-glucoside (TSG), a major component of PM, induces new hair growth in C57BL/6J mice [113]. Additionally, Shin et al, observed that PM extract (20 µg/mL) increased IGFBP2, PDGF, and VEGF expression in cultured hDPCs [30]. Alnus sibirica Fisch.…”
Section: Serenoa Repens Extractsmentioning
confidence: 99%
“…Polygonum multiflorum, usually known as "Heshouwu" in China and "Foti" in North America and East Asia, is a perennial vine-like herb of the family Polygonaceae, and it was officially listed in Chinese Pharmacopoeia and noted 1200 years ago, in the Tang dynasty, for its medicinal values [1]. To date, numerous pharmacological studies and clinical trials have demonstrated the biological activities of Polygonum multiflorum, including hair blackening activities, memory improvement, mitigation against other dysfunctions, anti-tumor activities, anti-inflammatory activities, anti-oxidation activities, anti-aging activities, lipid-lowering activities, immune regulation, and so on [2][3][4][5][6][7]. Therefore, it has been widely used not only as a medicine, but also as a popular tonic food and beverage in Asia and many other countries as a result of the general population's growing interests in phytonutrients and alternative medicines in recent decades [8].…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was observed in HFDPCs treated with the Hottuynia cordata extract. The expression of PDGF-AA and VEGF is increased by the phosphorylation of extracellular signal-regulated kinase (ERK) and protein kinase B (AKT) [20,21].…”
Section: Introductionmentioning
confidence: 99%